Role of prolyl hydroxylation in the molecular interactions of collagens - Rappu P.; Salo A.; Myllyharju J.; Heino J. (Portland Press Ltd, 2025)
Co- and post-translational hydroxylation of proline residues is critical for the stability of the triple helical collagen structure. In this review, we summarise the biology of collagen prolyl 4-hydroxylases and collagen prolyl 3-hydroxylases, the enzymes responsible for proline hydroxylation. Furthermore, we describe the potential roles of hydroxyproline residues in the complex interplay between collagens and other proteins, especially integrin and discoidin domain receptor type cell adhesion receptors. Qualitative and quantitative regulation of collagen hydroxylation may have remarkable effects on the properties of the extracellular matrix and consequently on the cell behaviour. © 2019 The Author(s).